2000
DOI: 10.1677/joe.0.1650207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of FSH and cell localization on dimeric inhibin-A secretion from bovine granulosa cells in culture

Abstract: We tested the hypotheses that the secretion of dimeric inhibin-A from cultured bovine granulosa cells is stimulated by FSH, and that antral cells secrete more inhibin-A than do mural cells. Cells from the antral or mural compartment of follicles were cultured in defined medium in two culture systems, and dimeric inhibin-A was measured by two-site ELISA or by Western immunoblotting. In the first culture system, dimeric inhibin-A secretion declined with time in culture, but was significantly (P<0·05) higher from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
3
5
0
Order By: Relevance
“…These discrepancies most likely reflect the fact that we used an assay that specifically detects dimeric inh A (␣-␤ A dimer), rather than ␣ subunit-directed RIAs as used by these authors. In agreement, Boudjemaa et al [48] recently reported an FSHinduced increase in inh A secretion by bovine granulosa cells cultured in conditions similar to ours; they also used a two-site immunoassay to specifically detect the ␣-␤ A dimer.…”
Section: Discussionsupporting
confidence: 91%
“…These discrepancies most likely reflect the fact that we used an assay that specifically detects dimeric inh A (␣-␤ A dimer), rather than ␣ subunit-directed RIAs as used by these authors. In agreement, Boudjemaa et al [48] recently reported an FSHinduced increase in inh A secretion by bovine granulosa cells cultured in conditions similar to ours; they also used a two-site immunoassay to specifically detect the ␣-␤ A dimer.…”
Section: Discussionsupporting
confidence: 91%
“…Studies in mammals indicate that activin can promote proliferation, inhA and B production (Lanuza et al 1999, Boudjemaa et al 2000, Findlay et al 2001 and FSH receptor expression by undifferentiated rat G cells (Hasegawa et al 1988, Xiao et al 1992) and, in turn, promote FSH-induced stimulation of LH receptor expression and upregulation of steroidogenesis (Hillier et al 1994). From the present observations, 'activin tone' appears to decrease progressively as small follicles grow from 1-2 mm to 9 mm, the approximate point of recruitment into the preovulatory hierarchy.…”
Section: Discussionmentioning
confidence: 99%
“…Because the early growth of the follicle cohort would be stimulated by FSH, increases in the concentration of inhibin A may have been caused primarily by the increased number of newly emerged and growing follicles. FSH has also demonstrated a direct action on inhibin A production by antral follicle granulosa cells in culture [28]. The dominant follicle was approximately 8-9 mm in diameter on the day of peak plasma concentrations of inhibin A.…”
Section: Discussionmentioning
confidence: 99%